THE COLLABORATION STRATEGY BETWEEN PUPIL AND TEACHER ON NURSING COMMUNITY TO IMPROVE THE BEHAVIOUR OF HEALTHY AND HYGIENIC LIFE TO THE WHOLE SCHOOL-AGE CHILDREN - Muhamad Hasbi (poltekkes kemenkes mataram, 2017)
School-age children is a golden period for embeding the values of healthy and hygienic-life behaviour (PHBS). The objective of this scientific writing was to provide an overview about the implementation of collaboration strategy between pupil and teacher in improving the behaviour of healthy and hygienic life in school-age children by utilizing the management approach of community nursing services, community nursing care, and family nursing care through the integration of community as a partner model, comprehensive school health model, family center nursing model, and management theory. Participants were pupils of Madrasah Ibtidaiyah Terpadu (MIT) at Cisalak Pasar sub-village, Cimanggis District, Depok City. The result indicated there was a significant result to the improvement of knowledge, healthy behaviour skills, and the improvement of school role and the indepedence of family. This scientific paper is expected to be fundamental of health promotion programs for school-age children.